Religiously Motivated Consumer Boycott: The Impact on Brand Image, Product Judgment and Customer Loyalty - Abosag, Ibrahim (2015)
The purpose of this paper is to improve theoretical and empirical knowledge first of all, about the effect of consumer ethnocentrism and religious animosity towards a country on consumers’ boycott propensity; and second about the effect of boycotting on customer product judgment, brand image and loyalty.